For a housing debate that seeks land where it is needed. A commentary on the InWIS study “Housing Construction needs (more) land” - Eichhorn, Sebastian; Holl, Christian; Jehling, Mathias; Münter, Angelika; Pätzold, Ricarda; Preuß, Thomas; Verbücheln, Maic (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
This commentary addresses the findings of the study “Housing Construction Needs (More) Land: New Land Take and Infill Development Under Scrutiny”, published by Institute for Housing, Real Estate, Urban and Regional Development (InWIS) at the Ruhr University Bochum und der EBZ Business School Bochum on June 18, 2025. The study concludes that due to barriers to infill development, new land is required for housing construction, and that the 30-hectare land-saving target should be questioned. In our view, this blanket demand is misleading and steers the debate in the wrong direction. Our micro-level empirical evidence shows that housing demand is highly concentrated in growth centres and transport corridors, while other areas are stagnating. A blanket release of land would therefore fuel uncontrolled urban sprawl. Instead of short-sighted instruments, we call for a sustainable housing policy based on a valid, small-scale database. The challenges are local, but the solutions must be conceived regionally and organized cooperatively. We advocate for a planning culture that strengthens regional responsibility and manages development according to actual needs, instead of abandoning land conservation across the board.